Histamine activates an intracellular Ca2+ signal in normal human lung fibroblast WI-38 cells - Berra-Romani, Roberto; Vargaz-Guadarrama, Ajelet; Sánchez-Gómez, Josué; Coyotl-Santiago, Nayeli; Hernández-Arambide, Efraín; Avelino-Cruz, José Everardo; García-Carrasco, Mario; Savio, Monica; Pellavio, Giorgia; Laforenza, Umberto; Lagunas-Martínez, Alfredo; Moccia, Francesco (Frontiers in Cell and Developmental Biology, 2022)
Histamine is an inflammatory mediator that can be released from mast cells to induce airway remodelling and cause persistent airflow limitation in asthma. In addition to stimulating airway smooth muscle cell constriction and hyperplasia, histamine promotes pulmonary remodelling by inducing fibroblast proliferation, contraction and migration. It has long been known that histamine receptor 1 (H1R) mediates the effects of histamine on human pulmonary fibroblasts through an increase in intracellular Ca2+ concentration ([Ca2+]i), but the underlying signalling mechanisms are still unknown. Herein, we exploited single-cell Ca2+ imaging to assess the signal transduction pathways whereby histamine generates intracellular Ca2+ signals in the human fetal lung fibroblast cell line, WI-38. WI-38 fibroblasts were loaded with the Ca2+-sensitive fluorophore, FURA-2/AM, and challenged with histamine in the absence and presence of specific pharmacological inhibitors to dissect the Ca2+ release/entry pathways responsible for the onset of the Ca2+ response. Histamine elicited complex intracellular Ca2+ signatures in WI-38 fibroblasts throughout a concentration range spanning between 1 µM and 1 mM. In accord, the Ca2+ response to histamine adopted four main temporal patterns, which were, respectively, termed peak, peak-oscillations, peak-plateau-oscillations, and peak-plateau. Histamine-evoked intracellular Ca2+ signals were abolished by pyrilamine, which selectively blocks H1R, and significantly reduced by ranitidine, which selectively inhibits H2R. Conversely, the pharmacological blockade of H3R and H4R did not affect the complex increase in [Ca2+]i evoked by histamine in WI-38 fibroblasts. In agreement with these findings, histamine-induced intracellular Ca2+ signals were initiated by intracellular Ca2+ release from the endoplasmic reticulum through inositol-1,4,5-trisphosphate (InsP3) receptors (InsP3R) and sustained by store-operated Ca2+ channels (SOCs). Conversely, L-type voltage-operated Ca2+ channels did not support histamine-induced extracellular Ca2+ entry. A preliminary transcriptomic analysis confirmed that WI-38 human lung fibroblasts express all the three InsP3R isoforms as well as STIM2 and Orai3, which represent the molecular components of SOCs. The pharmacological blockade of InsP3 and SOC, therefore, could represent an alternative strategy to prevent the pernicious effects of histamine on lung fibroblasts in asthmatic patients.